The Role of Green Banking in Enhancing Profitability: Evidence from Indian Retail Banks - Mr Aditya Sanghavi (Researchers World - International Refereed Social Sciences Journal, 2025)
Purpose: This study provides an empirical investigation into the effect of Green Banking Practices on the profitability of selected Indian retail banks. Panel data were collected from secondary sources, specifically the annual reports of the top five retail banks in India, covering the period from the year two thousand twenty to two thousand twenty-two. The analysis explores how environmental sustainability initiatives undertaken by banks influence financial performance. The empirical evidence suggests that these banks are increasingly aware of the strategic importance of adopting environmentally responsible practices. Green Banking has emerged as a matter of relevance at the board level, with institutions gradually integrating climate change considerations into their strategic planning and operational execution. This shift has shown a favourable impact on overall profitability, indicating that sustainable practices are not only environmentally essential but also financially beneficial. To examine the relationship between the variables, the study employed regression analysis, where profitability served as the dependent variable and various Green Banking indicators acted as independent variables. The results contribute valuable insights that can inform policy development and encourage further academic inquiry into the intersection of environmental sustainability and financial performance in the banking sector.